The Darling Dahlias and the Texas Star [large type] - Albert, Susan Wittig (Albert, Susan Wittig. Darling Dahlias mysteries, 2013)
The Texas Star herself -- Miss Lily Dare, the "fastest woman in the world" -- is bringing her Dare Devils Flying Circus to Darling. Unfortunately, she's also bringing a whole lot of trouble and rumors are flying. As the Texas Star barnstorms into town, Liz and Verna Tidwell offer to help bring down a saboteur who may be propelled by revenge. Before it's all over, there will be plenty of black eyes and dark secrets revealed . . .